Polydimethylsiloxane-silane synergy enables dropwise condensation of low surface tension liquids - Rabbi, Kazi Fazle (2022)
Despite decades of research on promoting the dropwise condensation of steam, achieving dropwise condensation of low surface tension liquids remains a challenge. The few coatings reported to promote dropwise condensation of low surface tension liquids either require complex fabrication methods, are substrate dependent or have poor scalability. Here, the rational development of a coating, which is applicable to all conventionally used condenser metals, is presented by combining a low contact angle hysteresis polydimethylsiloxane with a low surface energy silane using atmospheric vapor phase deposition. The siloxane-silane coating enables the dropwise condensation of fluids with surface tensions as low as 15 mN m−1 in pure vapor conditions. This siloxane-silane coating enables a 274%, 347%, and 636% heat transfer enhancement during ethanol, hexane, and pentane condensation, respectively, when compared to filmwise condensation on the same un-coated surfaces. Furthermore, this coating exhibits 15 days of steady dropwise condensation with no apparent signs of coating degradation. This study not only demonstrates the possibility of achieving stable dropwise condensation of low surface tension fluids on scalable, structure-less surfaces, it also develops design principles for creating facile, substrate-independent, durable, and scalable omniphobic coatings for a plethora of applications.